Article 9 Water Framework Directive: Do we really need to calculate environmental and resource costs? - Erik Gawel (Helmholtz-Zentrum für Umweltforschung (UFZ), 2014)
Article 9 of the EU Water Framework Directive (WFD) requires Member States to take account of the principle of recovery of the costs of water services, including environmental and resource costs (ERCs). Whilst legally the Member States have broad scope for discretion when applying Article 9, the idea that the EU legislator has effectively assigned the Member States a mathematical task to determine the level of cost recovery achieved for environmental and resource costs as well is increasingly gaining ground in the Common Implementation Strategy (CIS) process. The present paper shows that this strict interpretation of taking account of environmental and resource costs has no basis in Article 9, is conceptually misleading, and could even prove counter-productive for the practical application of water protection.
Keywords: 330